PENGEMBANGAN MEDIA FLASHCARD DALAM PEMBELAJARAN PENDIDIKAN PANCASILA KELAS III SDN LIMPUNG 01 - Anni Mustofiyah; Khusnul Fajriyah; M. Yusuf Setia Wardana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop flashcard learning media for the Pancasila Education subject in third-grade elementary school and to determine the feasibility level of the developed media. This research uses the Research and Development (R&D) method with the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. However, this research was only conducted up to the implementation stage. The research subjects were third-grade students at SD Negeri Limpung 01. Data collection techniques used validation questionnaires from media experts, material experts, as well as teacher and student response questionnaires. The results showed that the flashcard media obtained a media expert validation percentage of 86.8% (very valid category) and material expert validation of 93.8% (very valid category). Furthermore, teacher and student responses showed a very good category. Based on these results, the flashcard learning media is declared suitable for use as an alternative learning medium for Pancasila Education in elementary schools.